(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge and practice regarding dengue fever and factors associated with dengue prevention behaviour among resident students of a university in Hanoi in 2023. Subject and method: A cross-sectional study was conducted with 198 resident students of a university in Hanoi. Results: The mean score of knowledge and practice items was 12.21 out of total 29 points and 6.21 out of total 21 points, respectively. 52.5% and 54.5% of participants had adequate knowledge and practice regarding Dengue fever. Multivariable logistic regression analysis showed that students with adequate knowledge or received Dengue fever information from at least two communication channels had higher odds of achieving adequate practices regarding DF prevention, while students majoring in technology had lower odds of achieving adequate practice. Conclusion: The proportion of participants with adequate knowledge and practice regarding Dengue fever prevention were still low. Factors associated with the prevention practice include: knowledge, major, and receiving information about Dengue fever from at least two communication channels.